Implementation of Apriori Algorithm in Determining the Layout of Items - Putry, Yollanda; Andri Agus, Raja Tama; Sena, Maulana Dwi (Indonesian Journal of Artificial Intelligence and Data Mining, 2025)
Shopping at mini markets is now becoming popular as people's shopping orientation changes. This results in consumers preferring to shop in modern markets rather than to stalls or traditional shops. Because consumers want to shop comfortably and practically or in terms of finding goods in an easy way and knowing the location of the desired item. Risaga Jaya is a retail business that sells various needs such as staples, cosmetics, stationery, various snacks, During its operation, many goods are not in demand and there is a buildup of goods in the warehouse because there is no strategy for placing the position of goods that are more attractive to consumers. The purpose of this research is to create a strategy for placing goods to maximize sales using data mining with the apriori algorithm. By using the apriori algorithm, it can organize and organize the layout of an item by bringing related items closer together so that it can increase sales at the store based on consumer purchasing patterns, namely if consumers buy chitato then buy snack candy with a support given of 10% and a confidence given of 75%.